Design of Fuel Monitoring Tool with Runhour Genset and Controlling Genset Room Based on Internet of Things - Fitriani, Fenny; Waluyo, Waluyo; Rasyid, Abdul; Adzikirani, Adzikirani; Mustafa, Lis Diana (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
PT Telkom Indonesia, a telecommunications company, relies on Genset as a backup power source when the main power supply fails. To ensure efficient operation, the company uses an internet of things-based monitoring tool that utilizes various sensors. Ultrasonic sensor A02YYUW monitors the fuel level in the tank as it requires a supply of at least 3000L. The PZEM-004T sensor calculates the generator run time and power consumption to ensure it stays within the safe limits of less than 90 minutes per day and <500 kVA. In addition, the monitoring system keeps an eye on the generator room temperature to prevent overheating and component damage with a temperature limit of 36°C. All information collected by the sensors can be accessed through the website, making it easier for personnel to monitor and control maintenance. Test results show the functionality of the system, successfully measuring fuel levels, detecting runtime and power consumption, and controlling the fan through the website. The A02YYUW sensor measured the fuel depth of 82 cm and then converted it to volume, which is 2096 liters. Then, runhours were detected at 13 minutes with a power value that changes based on the load factor from 52.50 vA - 74.50 vA. For the condition of the generator room temperature, the lowest detected is 29.80°C to 40.70°C which requires turning on the fan to stabilize the room temperature.